Integrasi Sosial Muslim-Tionghoa Studi atas Partisipasi PITI DIY dalam Gerakan Pembauran - Fahmi Rafika Perdana (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Agenda ethnic assimilation in Indonesia often take a lot ofattention, given the realities of multi-ethnic population.Assimilation pri and nonpri or between ethnic Chinese and theNatives have been made parties to create lasting socialintegration. One of them through the Islamization of the ethnicChinese. Associated with it, PITI who organized ethnic-ChineseMuslims, have a lot of work in the middle of complexchallenges. Various cases of ethnic violence in various cities, theMay case `98, discrimination administration services, as well asthe latent threat related to the socio-economic gap has provedthe magnitude of the challenge for assimilation movement.Apparently, humans live in a world narrowed ethnicity andgrim. This article photographing PITI organizational dynamicsand participation in the assimilation movement, accompaniedby an analysis of the drivers and internal and externalconstraints confronting. Laborious the ethnic assimilationagenda in Indonesia, the handling is one of the main pillars instrengthening national unityKeyword: Integrasi sosial, Muslim Tionghoa, Gerakan Pembauran